Functional consequences of sulfhydryl modification in the pore-forming subunits of cardiovascular Ca2+ and Na+ channels - Chiamvimonvat, Nipavan; O’Rourke, Brian; Kamp, Timothy J.; Kallen, Roland G.; Hofmann, Franz; Flockerzi, Veit; Marban, Eduardo (Circulation research, 1995)
Abstract The structure and function of many cysteine-containing proteins critically depend on the oxidation state of the sulfhydryl groups. In such proteins, selective modification of sulfhydryl groups can be used to probe the relation between structure and function. We examined the effects of sulfhydryl-oxidizing and -reducing agents on the function of the heterologously expressed pore-forming subunits of the cloned rabbit smooth muscle L-type Ca2+ channel and the human cardiac tetrodotoxin-insensitive Na+ channel. The known sequences of the channels suggest the presence of three or four cysteine residues within the putative pores of Ca2+ or Na+ channels, respectively, as well as multiple other cysteines in regions of unknown function. We determined the effects of sulfhydryl modification on Ca2+ and Na+ channel gating and permeation by using the whole-cell and single-channel variants of the patch-clamp technique. Within 10 minutes of exposure to 2,2′-dithiodipyridine (DTDP, a specific lipophilic oxidizer of sulfhydryl groups), Ca2+ current was reduced compared with the control value, with no significant change in the kinetics and no shift in the current-voltage relations. The effect could be readily reversed by 1,4-dithiothreitol (an agent that reduces disulfide bonds). Similar results were obtained by using the hydrophilic sulfhydryl-oxidizing agent thimerosal. The effects were Ca2+-channel specific: DTDP induced no changes in expressed human cardiac Na+ current. Single-channel Ba2+ current recordings revealed a reduction in open probability and mean open time by DTDP but no change in single-channel conductance, implying that the reduction of macroscopic Ca2+ current reflects changes in gating and not permeation. In summary, the pore-forming (α1) subunit of the L-type Ca2+ channel contains functionally important free sulfhydryl groups that modulate gating. These free sulfhydryl groups are accessible from the extracellular side by an aqueous pathway.
Gesehen am 13.02.2025
Im Titel sind "2+" und"+" hochgestellt